Prognostic factors and real-life applicability of prognostic models for patients with bone metastases of carcinoma - Kaan Ali Dalkir; Akif Mirioglu; Bugra Kundakci; Melih Bagir; Mehmet Ali Deveci; Hilmi Serdar Ozbarlas (Acta Orthopaedica et Traumatologica Turcica)
Objective: This study aimed to investigate the factors affecting the survival of patients with bone carcinoma metastases and assess the clinical applicability of existing prognostic models.